A Study of Consumer Perception for Investment Towards Different Options Especially in Realestate and Gold - Jain , Megha; Shukla, Abhikrati (Gyan Management Journal, 2017)
Investment is an activity that is engaged in by people who have savings i.e. investments are made from savings, or in other words people invest their savings.A variety of investment options are available such as bank, Gold, Real estate, post services, mutual funds & so on. Investors are investing their money with the different objectives such as profit, security, appreciation, Income stability. Researcher has studied the different avenues of investments as well as the factors while selecting the investment with the sample size of 150 consumers by conducting the survey through questionnaire in Indore, India. The study is based on personal interviews with the consumers, using a structured questionnaire. Actually, the present study identifies the preferred investment avenues among the individual investors. The study is based on primary sources of data which are collected by distribution of a close ended questionnaire. The data has been analyzed using pie charts and bar graphs. The study concluded that consumer prefers investing in gold as it is more secure and very high return generating option. Then they prefer investing in real estate and least preference gives to equity.